Agricultural public policies and their impact on local development in the Campozano parish - Vera Mendiet, Winter Antonio; Useche Castro, Lelly María (Revista Minerva, 2025)
The objective of the research was to propose a methodology to evaluate agricultural public policies in the Campozano parish, Manabí province, Ecuador, contributing to local development. The research, with a descriptive approach, characterized the processes and structures related to territorial management and agricultural policies. The results indicated that, despite being aligned with the National Development Plan, the policies presented deficiencies in their execution, especially in the coverage of goals and local participation. The indicators showed an 88.89% progress in soil conservation, 66.67% in production and road connectivity, and 80% in organizational policies. It was concluded that the lack of coordination and community participation limited the effectiveness of the policies. It was recommended to implement a monitoring system, promote citizen participation and develop a strategic plan to improve the competitiveness of Campozano and its alignment with national objectives.